The Influence of Social Media Marketing on Digital Banking Consumer Behavioral Intention Through Brand Experience and Relationship Marketing - Rizal, Rusma; Khairunissa, Amaliah (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This research aims to determine the influence of social media marketing on the behavioral intention of digital banking consumers through brand experience and relationship marketing in the city of Palembang. This research uses a quantitative approach to explain the position of the variables studied and the relationship between one variable and another. This research is intended to test hypotheses that have been previously formulated. The results of this research will explain the causal relationship between variables through hypothesis testing. In this research, the analysis method used is path analysis with path analysis using the SmartPLS program. The results of this research found that 1) There is a partial influence Brand experience on Behavioral intention 2) There is an influence of Relationship marketing on Behavioral intention 3) There is an influence of Social media marketing on Behavioral intention 4) The moderating role of Relationship marketing has no influence between Social media marketing on Behavioral intention 5) The Moderating role of Brand experience has no influence between Social media marketing on Behavioral intention.